Dependence of the product's phase composition on the ratio of precursors in plasmodynamic synthesis of titanium diboride; Химия и химическая технология в XXI веке - Pogorelova S. O. (Химия и химическая технология на иностранном языке, 2018)
Заглавие с экрана